THE POTENTIAL USE OF COMPUTERS IN ONLINE LEARNING IN THE DIGITAL AGE - Nur Rahmad Yahya Wijaya (ADISAM Publisher, 2026)
This article analyses the potential use of computers in online learning in the digital age through two main dimensions: accessibility-flexibility and interactivity-innovation. Computer accessibility enables inclusive education to reach remote areas of Indonesia via offline download features, multi-device support, and multi-language personalisation, with an increase in student participation of up to 60% based on post-pandemic literature. Interactivity through AR/VR 3D overlays, gamification, AI chatbots, and virtual business simulations increases memory retention by 55%, critical thinking, and entrepreneurship skills by 60%, transforming passive learning into a dynamic student-centred ecosystem. Recommendations from this research include the need for national digital literacy teacher training, hybrid cloud infrastructure, and integration of the Merdeka Curriculum to realise Indonesia Emas 2045 through equitable quality education.